SEP-like genes of Gossypium hirsutum promote flowering via targeting different loci in a concentration-dependent manner - Chen, Liting; Yan, Yuanyuan; Ke, Huifeng; Zhang, Zihao; Meng, Chengsheng; Ma, Limei; Sun, Zhengwen; Chen, Bin; Liu, Zhengwen; Wang, Guoning; Yang, Jun; Wu, Jinhua; et al. (Frontiers in Plant Science, 2022)
SEP genes are famous for its function in morphological novelty of bisexual flowers. Although diverse functions of SEP genes were reported, only the regulatory mechanisms underlying floral organ development have been addressed. In this study, we identified SEP-like genes in Gossypium and found that SEP3 genes duplicated in diploid cotton varieties. GhSEP4.1 and GhSEP4.2 were abundantly transcribed in the shoot apical meristem (SAM) but only GhSEP4.2 expressed in the leaf vasculature. The expression pattern of GhSEPs in floral organs was conserved with that of homologs in Arabidopsis, except for GhSEP2 that was preponderantly expressed in the ovules and fibers. Overexpression and silencing of each single GhSEP gene suggested their distinct role in promoting flowering via direct binding to GhAP1 and GhLFY genomic regions. The curly leaf and floral defects in overexpression lines with higher expression of GhSEP genes revealed the concentration-dependent target gene regulation of GhSEP proteins. Moreover, GhSEP proteins were able to dimerize and interact with flowering time regulators. Together, our results suggest the dominant role of GhSEP4.2 in leaf to promote flowering via GhAP1-A04, and differently accumulated GhSEP proteins in SAM alternately participate in forming the dynamic tetramer complexes to target at different loci of GhAP1 and GhLFY to maintain the reproductive growth. The regulatory role of cotton SEP genes reveals their conserved and diversified functions.